2013
DOI: 10.1021/ed3002336
|View full text |Cite
|
Sign up to set email alerts
|

A Teaching Sequence for Learning the Concept of Chemical Equilibrium in Secondary School Education

Abstract: A novel didactic sequence is proposed for the teaching of chemical equilibrium. This teaching sequence takes into account the historical and epistemological evolution of the concept, the alternative conceptions and learning difficulties highlighted by teaching science and research in education, and the need to focus on both the students’ learning process and the knowledge to learn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…In addition to the studies in which chemistry teaching is carried out by using different GOs together, it is seen that there are studies in which teaching is carried out with a single GO type in the teaching of chemistry subjects and such studies are relatively more common. While it is seen that concept maps are the most used GO types in such studies (Aguiara & Correia, 2016;Ghirardi et al, 2014;Moyses, Rivet, &. Fahlman, 2010;Nakiboğlu & Ertem, 2010;Polancos, 2013;Singh & Moono, 2015), mind map (Ezeh & Okeke, 2018;Nyagblormase et al, 2021), Vee diagram (Chamizo, 2012;, Nakiboğlu & Nakiboğlu, 2017cPolancos, 2013), flow diagram (Davidowitz, B & Rollnick, 2001;, decision map (DeMeo, 2007) are the other GO types used.…”
Section: The Rationale and Research Questions Of The Studymentioning
confidence: 99%
“…In addition to the studies in which chemistry teaching is carried out by using different GOs together, it is seen that there are studies in which teaching is carried out with a single GO type in the teaching of chemistry subjects and such studies are relatively more common. While it is seen that concept maps are the most used GO types in such studies (Aguiara & Correia, 2016;Ghirardi et al, 2014;Moyses, Rivet, &. Fahlman, 2010;Nakiboğlu & Ertem, 2010;Polancos, 2013;Singh & Moono, 2015), mind map (Ezeh & Okeke, 2018;Nyagblormase et al, 2021), Vee diagram (Chamizo, 2012;, Nakiboğlu & Nakiboğlu, 2017cPolancos, 2013), flow diagram (Davidowitz, B & Rollnick, 2001;, decision map (DeMeo, 2007) are the other GO types used.…”
Section: The Rationale and Research Questions Of The Studymentioning
confidence: 99%
“…Chemistry is said to exist at three operational levels: the macroscopic, microscopic, and the symbolic representation (Johnstone, 2000;Taber, 2013;Talanquer, 2011). Effective teaching strategies that assist learners to switch between operational levels are considered very necessary in chemistry (Ghirardi, Marchetti, Pettinari, Regis, & Roletto, 2014;Johnstone, 2000;Talanquer, 2011).…”
Section: Theoretical Framework and Related Literature Reviewmentioning
confidence: 99%
“…Informal feedback from the students revealed that they valued having the virtual “chalk and talk” discussions. Through these discourses, the instructor was able to identify and clarify students’ conceptual difficulties and misunderstandings pertaining to topics such as chemical equilibria, which is considered to be one of the more complex concepts in chemistry …”
Section: Introductionmentioning
confidence: 99%
“…Through these discourses, the instructor was able to identify and clarify students' conceptual difficulties and misunderstandings 12 pertaining to topics such as chemical equilibria, which is considered to be one of the more complex concepts in chemistry. 13 Are You Paying Attention, and Do You Understand?…”
Section: ■ Introductionmentioning
confidence: 99%